Alemtuzumab and Sirolimus in Renal Transplantation: Six‐Year Results of a Single‐Arm Prospective Pilot Study. Issue 3 (7th January 2014) - Sutherland, A. I.; Akhtar, M. Z.; Zilvetti, M.; Brockmann, J.; Ruse, S.; Fuggle, S. V.; Sinha, S.; Harden, P.; Friend, P. J.
<x xml:space="preserve">Abstract</x> mTOR inhibitors avoid calcineurin nephrotoxicity, but sirolimus de novo is associated with unacceptable side effects and higher rejection rates. We have investigated a modified strategy: alemtuzumab induction with tacrolimus and mycophenolate maintenance, switching from tacrolimus to sirolimus at 6 months and stopping mycophenolate at 12 months. Here, we report the 6‐year follow‐up of 30 patients prospectively recruited to this single‐arm pilot study and compare outcomes to a matched contemporaneous control group of 30 patients who received standard induction and calcineurin‐inhibitor‐based immunosuppression. Six‐year patient and graft survival were 83% and 80% (alemtuzumab) versus 77% and 70% (control). Rejection rates in the first 6 months were similar in alemtuzumab (6.6%) and control groups (10%). A higher than expected incidence of rejection in the alemtuzumab group following cessation of mycophenolate at 1 year (17%) was mitigated in later patients by retaining low dose mycophenolate. Mean eGFR was higher in the alemtuzumab group at all time points but not significantly (p = 0.16). Tacrolimus levels in the first 6 months were significantly higher in the contemporaneous control group (p < 0.001). Alemtuzumab induction with initial treatment with tacrolimus enables conversion to sirolimus without the side effects and incidence of acute rejection seen in earlier protocols.